Learning Method For Local Identity Through Traditional Food In Tulungagung â€œAyam Lodhoâ€ - Ellyzabethania, Gladera Ellyzabethania; Khusyairi, Jhony Alfian; Rosyidah, Usma Nur Dian (Mahesa Research Center, 2023)
This research aims to look into the traditional food of Tulungagung. Ayamlodho is a traditional Tulungagung dish that is very popular among the locals. AyamLodho is also served with urap-urap and has a distinctive grilled and spicy sauce. AyamLodho became popular among Tulungagung residents as the main course menu at special events. The purpose of this research is to examine the meaning of AyamLodho as well as the meaning of the word Lodho. This study employs a qualitative approach. In-depth interviews, observation, document studies, literature studies, and recording sources are all used to collect data. Functional analysis is a method for deciphering the meaning of Ayamlodhofood.The goal of this review is to analyze the meaning of the traditional food